TREND TO APPLY TOULMIN ARGUMENT PATTERN (TAP) TO LEARNING PHYSICS IN THE ABILITY TO PRACTICE THE ARGUMENT AND UNDERSTANDING CONCEPTS - NIKI BAGUS WAHYUNE S, MUCHAMMAD; ADMOKO, SETYO (Inovasi Pendidikan Fisika, 2020)
This study was conducted in order to investigate how the argument was positioned in the publication of academic journals in Indonesia and abroad from 2013-2020. The method for the content analysis of this journal is explained using quantitative and qualitative techniques to illustrate the trend of the application of Toulmin Argument Pattern (TAP) on physical learning in training the ability of arguments and understanding of concepts. The type of research implemented is systematic literature review (SLR). The subject of this research is research data in several journals that have been published nationally and internationally. The data analysis techniques in this study are based on the stages of similarity, inequality, giving views, comparing, and summarizing. Based on data derived from published journal results indicating that the use of TAP implementation in physics learning can improve the ability of concepts and comprehension with different outcomes, one of the contributions of this analysis is the illustration that the researchers implementing TAP in physics learning have a positive impact on learners regarding their increasingly better argument ability. It needs to be done for a long time so that the learners are accustomed to making arguments as supporting for scientific investigation activities in emphasizing evidence-based justification for making claims. From the research results can be concluded that TAP can be applied further to learning physics on the material as well as other subjects because it is in accordance with the curriculum developed in Indonesia.